Socialization A Multidimensional Perspective - Morese, Rosalba; Palermo, Sara; Nervo, Juri (IntechOpen, 2018)
This is the first book that highlights how socialization is experienced as being a complex concept in everyday life in various countries of the world. The book represents the first attempt to provide an original and multidimensional definition of socialization that takes into account the contribution of different disciplines, such as philosophy, psychology, sociology, education, and even architecture, to underline its importance as a key aspect of human experience. Therefore, it represents an extraordinary opportunity to outline new horizons in the field.